New Horizons in Osteoporosis Management - El Miedany, Yasser; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2022)
This book provides a review of the most recent data on osteoporosis and bone health, presenting a vision of diagnosis and management for the year 2021 and beyond. It covers all pertinent aspects of bone health including diagnosis, fracture prevention, optimized practice, impaired orthostasis, and falls. The book examines recent developments in therapeutics, including goal-directed therapy, individualizing therapy, sequential and combined therapies, pharmaceuticals, and anabolic vs. antiresorptive therapy. In addition, it provides an in-depth overview of osteoporosis and bone health in complex patients, covering Duchene dystrophy, renal failure, periodontal diseases, and steroid-induced osteoporosis as well as considerations for pediatric populations and men. New Horizons in Osteoporosis Management is an essential resource for physicians and related professionals, residents, fellows, graduate students and nurses in rheumatology, endocrinology, radiology, pediatrics, primary care, and internal medicine. .
Part I. Bone Health: Towards Better Bones -- 1. Bone Health and Osteoporosis -- 2. Recognizing People at Highest Risk of Fracture -- 3. T-score as an Indicator of Fracture Risk -- Part II. Osteoporosis Diagnosis: Clinician$1 (Bs Guide -- 4. Current Imaging Techniques -- 5. The Challenges of Diagnosing Osteoporosis -- 6. The Role of the Radiographer in DXA Scan Service -- 7. Pitfalls in DXA Scanning -- Part III. Fracture Prevention -- 8. Osteoporosis Update for Primary Care Physicians -- 9. Fracture Liaison Service -- 10. Imminent Fracture Risk -- Part IV. Bone Health: Towards Optimized Practice -- 11. Guidelines for Management of Osteoporosis -- 12. The Role of Pharmacist in Osteoporosis Treatment -- 13. A Treatment Gap in Osteoporosis Management -- 14. Denosumab Vs Bisphosphonates -- 15. Romosozumab: Rebuilding the Bone Strength -- 16. Recent Trends in Osteoporosis Management -- 17. Optimizing Sequential and Combined Osteoporosis Therapy -- Part V. Bone Health: Osteoporosis Treatment -- 18. Goal Directed Therapy -- 19. Long Term Osteoporosis Management -- 20. Complications of Osteoporosis Therapy -- Part VI. Bone Health in Complex Patients -- 21. Pediatric Osteoporosis -- 22. Osteoporosis in Duchenne dystrophy -- 23. Osteoporosis in Renal Failure -- 24. Steroid Induced Osteoporosis -- 25. Osteoporosis in Men -- 26. Periodontal Diseases -- 27. Hormone Antagonist Therapy -- Part VII. Bone Health, Falls, and Impaired Orthostasis -- 28. Disequilibrium -- 29. Dysautonomia -- 30. Sarcopenia -- 31. Advances in the Assessment and Management of Falls.s
Keywords: Internal medicine; Orthopedics; Internal Medicine; Internal Medicine; Orthopaedics; Osteoporosis -- therapy; Osteoporosis